Peran Trust Dalam Memediasi Pengaruh Electronic Word Of Mouth (E-Wom) Terhadap Keputusan Pembelian (Studi Kasus Pada Platfrom Marketplace Tokopedia Di Kota Pontianak) - Rikardus Reki; Maulana Filani Rizal; Arweni Ibrahim (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2026)
In the digital era, electronic word of mouth (eWOM) has become a key factor in shaping consumer behavior on e-commerce platforms, especially in Indonesia, where marketplaces like Tokopedia dominate online transactions with a user base reaching hundreds of millions. However, the influence of electronic word of mouth is often mediated by consumers' level of trust in the platform and its recommendations. This study aims to analyze the role of trust as a mediating variable in the relationship between electronic word of mouth and purchasing decisions among Tokopedia users in Pontianak City. This study aims to analyze the role of trust in mediating the influence of electronic word of mouth on purchasing decisions, using a case study on the Tokopedia marketplace platform in Pontianak City. This study used a quantitative method with a descriptive approach. Data were obtained through questionnaires distributed to 137 respondents who had made purchases on the Tokopedia marketplace platform in Pontianak City. Data analysis was performed using the Partial Least Squares-Structural Equation Modeling method using SmartPLS 4.1 software. The results of this study indicate that electronic word of mouth has no effect, while trust has a significant effect on purchasing decisions. Furthermore, trust was shown to significantly mediate the relationship between electronic word of mouth and purchasing decisions. These findings confirm that consumer trust plays a significant role in enhancing purchasing decisions through positive reviews, ratings, and customer comments on the Tokopedia marketplace platform.